The impact of salary and job safety on the work productivity of employees at PTPN V Tanjung Medan Oil Palm Plantations / DTM Al Azhari Solahuddin and M Tahir - Solahuddin, DTM Al Azhari; M Tahir (Center for Islamic Philantrophy & Social Finance (CIPSF), 2024)
The issue in this exploration is the compensation that is still underneath the provincial The lowest pay permitted by law (UMKR) is due to the absence of familiarity with PTPN V oil palm manors in Tanjung Medan, Kec. Pujud Rokan Hilir. This sort of exploration utilizes quantitative examination. The population in this study was 153 workers, with an example of 153 representatives. Equation with the assistance of the SPSS Variant 22 information handling program for Windows The information investigation utilized numerous straight relapses, and the accompanying outcomes were found: The consequences of the incomplete test (t test) on the compensation variable are t-count 3.109 > t-table 2.0129, and that really intends that there is a positive and huge effect on PTPN V oil palm manor representative execution, while for the yield motivator variable, the halfway test (t trial) of t-count 1.936 > t-table 2.0129 Sig. 0.00 > 0.05 intends that there is an impact of word-related wellbeing security on the presentation of PTPN V oil palm ranch workers. In view of the consequences of the concurrent test, the Fcount esteem is 15.108 while the Ftable is 2.81 (15.108 > 0.05), while the huge level is under 0.05, to be specific (0.00 <0.05), and that truly intends that there is a critical constructive outcome between the impact of pay and word-related wellbeing security on worker execution. In view of the trial of the coefficient of assurance, the value of the changed R square is 0.496 (49.6%). This implies that the capacity of the autonomous variable in this study influences the dependent variable by 49.6%, while the excess 50.4% can be made sense of by factors other than the free factor.